The Evaluation of Substituting Native Grass with Citronella Waste on the Digestibility of Dry Matter, Organic Matter, and Crude Protein in Ruminants Feeding - Tri; Sapoti, Yunita; Ali Akbar, Syahro; Basyirun, Fajri; Surtina, Dara (Universitas Veteran Bangun Nusantara, 2024)
This study aims to determine the effect of substituting native grass with citronella waste on the digestibility of ruminants' dry matter, organic matter, and crude protein. A completely randomized design with 6 (six) treatments and 3 (three) replications is used in this research. The treatments were as follows: P1 = 50% native grass + 0% citronella waste + 50% concentrate; P2 = 40% native grass + 10% citronella waste + 50% concentrate; P3 = 30% native grass + 20% citronella waste + 50% concentrate; P4 = 20% native grass + 30% citronella waste + 50% concentrate; P5 = 10% native grass + 40% citronella waste + 50% concentrate; and P6 = 0% native grass + 50% citronella waste + 50% concentrate. The results showed that substituting native grass with citronella waste significantly affects (P<0.01) the digestibility of dry matter, organic matter, and crude protein. The highest digestibility values were observed in the treatment using 100% native grass, with dry matter digestibility at 52.67%, organic matter at 56.58%, and crude protein at 67.55%. The study concludes that while native grass cannot be entirely replaced by citronella waste, it can substitute up to 50% of the complete feed when native grass availability is limited.